Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^8+3x^4+4\)
\(=\left(x^8-x^6+2x^4\right)+\left(x^6-x^4+2x^2\right)+\left(2x^4-2x^2+4\right)\)
\(=x^4\left(x^4-x^2+2\right)+x^2\left(x^4-x^2+2\right)+2\left(x^4-x^2+2\right)\)
\(=\left(x^4+x^2+2\right)\left(x^4-x^2+2\right)\)
\(4x^4+4x^3+5x^2+2x+1\)
\(=\left(4x^4+2x^3+2x^2\right)+\left(2x^3+x^2+x\right)+\left(2x^2+x+1\right)\)
\(=2x^2\left(2x^2+x+1\right)+x\left(2x^2+x+1\right)+\left(2x^2+x+1\right)\)
\(=\left(2x^2+x+1\right)^2\)
= x^8 - x^7 + x^6 - x^5 + x^4 + x^7 - x^6 + x^5 - x^4 + x^3 + x^6 - x^5 + x^4 - x^3 + x^2 + x^5 - x^4 + x^3 - x^2 + x + x^4 - x^3 + x^2 - x + 1
= (x^8 - x^7 + x^6 - x^5 + x^4) + (x^7 - x^6 + x^5 - x^4 + x^3) + (x^6 - x^5 + x^4 - x^3 + x^2) + (x^5 - x^4 + x^3 - x^2 + x) + (x^4 - x^3 + x^2 - x + 1)
= x^4(x^4 - x^3 + x^2 - x + 1) + x^3(x^4 - x^3 + x^2 - x + 1) + x^2(x^4 - x^3 + x^2 - x + 1) + x(x^4 - x^3 + x^2 - x + 1) + (x^4 - x^3 + x^2 - x + 1)
= (x^4 + x^3 + x^2 + x + 1)(x^4 - x^3 + x^2 - x + 1)
2222222222222222222222222222222222222222222222222222222222223333333
\(x^{16}+x^8-2=x^{16}-x^8+2x^8-2=x^8\left(x^8-1\right)+2\left(x^8-1\right)\)
\(=\left(x^8+2\right)\left(x^8-1\right)=\left(x^8+2\right)\left(x^4+1\right)\left(x^4-1\right)\)
\(=\left(x^8+2\right)\left(x^4+1\right)\left(x^2+1\right)\left(x^2-1\right)\)
\(=\left(x^8+2\right)\left(x^4+1\right)\left(x^2+1\right)\left(x+1\right)\left(x-1\right)\)
\(x^3+x^2+2x+8\)
\(=x^3+2x^2-x^2-2x+4x+8\)
\(=x^2\left(x+2\right)-x\left(x+2\right)+4\left(x+2\right)\)
\(=\left(x+2\right)\left(x^2-x+4\right)\)